2021
DOI: 10.1002/anie.202108170
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite‐Tailored Active Site Proximity for the Efficient Production of Pentanoic Biofuels

Abstract: Biofuel production can alleviate reliance on fossil resources and thus carbon dioxide emission. Hydrodeoxygenation (HDO) refers collectively to a series of important biorefinery processes to produce biofuels. Here, well‐dispersed and ultra‐small Ru metal nanoclusters (ca. 1 nm), confined within the micropores of zeolite Y, provide the required active site intimacy, which significantly boosts the chemoselectivity towards the production of pentanoic biofuels in the direct, one‐pot HDO of neat ethyl levulinate. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…To further quantify the fraction of the Ru clusters encapsulated inside the zeolite cavities, hydrogenation tests with two probing molecules , toluene (kinetic diameter: 0.55 nm, accessible into the cavities of MFI) and 1,3,5-triisopropylbenzene (TIPB, kinetic diameter: 0.85 nm, inaccessible into the cavities of FAU), with different sizes have been performed. 48 To suppress Brønsted acid site (BAS)-induced side reactions (i.e., TIPB dealkylation and toluene disproportionation), the BAS of all samples was further removed by an ion-exchange treatment with sodium cations (Na + ) before the hydrogenation tests. The analysis of Fourier transform-infrared spectroscopy (FT-IR) of pyridine adsorption confirms the removal of all the BASs in these samples (Figure S7).…”
Section: Validation Of Metal Encapsulationmentioning
confidence: 99%
“…To further quantify the fraction of the Ru clusters encapsulated inside the zeolite cavities, hydrogenation tests with two probing molecules , toluene (kinetic diameter: 0.55 nm, accessible into the cavities of MFI) and 1,3,5-triisopropylbenzene (TIPB, kinetic diameter: 0.85 nm, inaccessible into the cavities of FAU), with different sizes have been performed. 48 To suppress Brønsted acid site (BAS)-induced side reactions (i.e., TIPB dealkylation and toluene disproportionation), the BAS of all samples was further removed by an ion-exchange treatment with sodium cations (Na + ) before the hydrogenation tests. The analysis of Fourier transform-infrared spectroscopy (FT-IR) of pyridine adsorption confirms the removal of all the BASs in these samples (Figure S7).…”
Section: Validation Of Metal Encapsulationmentioning
confidence: 99%
“…Ethyl levulinate (EL) is an important type of biomass platform compounds. Upgrading EL into various valuable chemicals has attracted significant attention ( He et al., 2021 ; Luo et al., 2015 ; Xie et al., 2019 ). In this regard, Meerwein-Ponndorf-Verley (MPV) reduction of EL to produce γ-valerolactone (GVL) has been recognized as one of the most promising strategies ( Scheme S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The above catalytic processes for the conversion of LevA or Levs to Vals mainly proceeded via GVL owing to the facile intramolecular cyclization of the active intermediate 4-hydroxypentanoic acid ester. Recent work by Luo et al 87 revealed a different route for Val synthesis from EtLev, eliminating the formation GVL. They prepared a Ru/La-Y zeolite catalyst with sub-nanometer proximity of metal and acidic sites to obtain 96% EtVal + ValA yields directly from EtLev.…”
Section: Alkyl Valeratesmentioning
confidence: 99%